Optimasi Jarak Tanam dan Pemberian Asam Humat Untuk Meningkatkan Produksi Benih Jagung (Zea mays L.) - Adi Nuswantoro, Nugroho; Sulistiyono, Nantil Bambang Eko (Agropross : National Conference Proceedings of Agriculture, 2023)
Fluctuations in maize production make Indonesia often dependent on imports. Low productivity is one of the problems of low maize production. Increasing maize productivity can be supported by improving cultivation methods through increasing plant spacing and applying organic fertilizers. This study aims to determine the optimal optimization of plant spacing and complementary organic fertilizer to increase maize seed production. This research was conducted in the paddy field of Tegal Gede Village, Sumbersari Subdistrict, Jember Regency, this research used a factorial group randomized design with 2 factors and 3 replications. The first factor was the optimization of planting distance, namely 60 x 25 cm, 75 x 25 cm, and 90 x 25 cm, while the second factor was the application of humic acid, namely 10 kg/ha, 20 kg/ha, and 30 kg/ha. and 30 kg/ha. The results showed that the interaction of 90 x 25 cm spacing optimization and 30 kg/ha of humic acid on the parameters of corn cob weight and dry weight of kernels showed the best results. The parameter of seed production weight per hectare which gives a high amount in the treatment of optimization of plant spacing 60 x 25 cm and 20 kg/ha of humic acid with a yield of 6.2 tons